ANTESEDEN PERILAKU KONSUMTIF DI MASA PANDEMI COVID-19 - Dyah Fitriani; Hendro Setyono; Sarazfhiga Solehatin (Jurnal Fokus Manajemen Bisnis, 2023)
The development of e-commerce provides many conveniences for shopping consumers. Consumers are increasingly familiar with the online shopping system since the emergence of the covid-19 pandemic, which limited people's mobility, including shopping. This study analyzes student consumerism behavior regarding self-control, peers, and socioeconomic status. The sample in this study amounted to 180 students. The sampling technique used simple random sampling with a questionnaire to collect respondents' answers. The results of this study prove that peers have a positive effect on consumptive behavior. However, self control and socio-economic status have no effect on consumptive behavior.